SENSITIVITAS MAKRO EKONOMI TERHADAP INDEKS HARGA SAHAM GABUNGAN (IHSG): DILIHAT DARI PERSPEKTIF MONETER - Sukmawati, Dian; Komarudin, Mamay; Nurasiah, Iis; Munawaroh, Munawaroh (Jurnal Valuasi: Jurnal Ilmiah Ilmu Manajemen dan Kewirausahaan, 2025)
The Jakarta Composite Index (JCI) is an index that measures the performance of all stock prices, both common and preferred, listed on the Indonesia Stock Exchange (IDX). Some macroeconomic factors that have the potential to affect the movement of the JCI include inflation, BI rate, and exchange rates. This study aims to analyze the sensitivity of JCI to inflation, BI rate, and exchange rate during the period 2010-2023. The approach used is quantitative, with the population including all JCI, inflation, BI rate, and exchange rate data for 2010-2023. The method used is census, with samples in the form of quarterly closing price of JCI, inflation, BI rate, and exchange rate from 2010 to 2023, resulting in 56 observational data. The data analysis technique applied in this study is Error Correction Model (ECM) using EViews software version 12. The results showed that partially, JCI is not sensitive to inflation and BI rate, but JCI proved to be sensitive to exchange rates. Meanwhile, simultaneously, JCI is sensitive to inflation, BI rate, and exchange rate simultaneously with relevant statistical significance